ABSORPSI AIR KOMPOSIT SEMEN SEKAM PADI DENGAN PENAMBAHAN POZZOLAN ABU SEKAM PADI DAN KAPUR PADA MATRIKS SEMEN - . Bakri; . Baharuddin (Forestry Faculty of Universitas Hasanuddin, 2010)
This research aimed to determine the role of rice husk ash as pozzolanic material in reducing water absorption of rice husk cement composite. Rice husk ash obtained by burning rice husk conventionally in kiln drum. Preparation of water absorption testing samples was conducted according to ASTM C 140, while ASTM C 90 used to evaluate the desired water absorption. Rice husk ash as of 40 % significantly reduced water absorption of the composite, but only rice husk ash of 20 % dan 30 % fulfilled the ASTM C 90 requirement. Addition of lime in the mixture increased the water absorption. Key words: pozzolamic, water absorption, rick husk, rice husk ash.